Comparative simulation of crop productivity, soil moisture and nitrate-N leaching losses for intermediate wheatgrass and maize in Minnesota using the DSSAT model - Mulla, David J.; Tahir, Muhammad; Jungers, Jacob M. (Frontiers in Sustainable Food Systems, 2023)
Perennial grain crops are a potential alternative source of staple foods and animal forage that can also provide additional environmental benefits over annual crops. Intermediate wheatgrass (IWG; Thinopyrum intermedium) is a new perennial dual-use crop for grain and forage, with growing interest among stakeholders as it produces grain in a more environmentally sound manner than current annual crops. DSSAT model simulations were performed for maize and a new DSSAT model for IWG based on data collected from field studies conducted during 2013-2015 at three different locations, i.e., Lamberton, Waseca and Crookston using low (zero), medium (60-80 kg ha-1) and high fertilizer nitrogen (N) rates (120-160 kg ha-1). The DSSAT CERES-Maize and CROPGRO-PFM model used as the basis for simulating IWG was calibrated at the high N rate to predict the yield/biomass, soil water balance, and soil nitrogen balance in maize and IWG, respectively, for the medium and low N rate treatments. Model predictions for maize yield and IWG biomass (0.89≤ Nash Sutcliffe Efficiency≥0.58), soil profile moisture (0.81≤ NSE≥0.53) ranged from very good to satisfactory accuracy, while nitrate-N leaching losses (0.76≤ NSE≥0.43) ranged from very good to satisfactory for corn and the high N rate in IWG, with nearly satisfactory accuracy for IWG under the medium and zero N rates. Simulation results indicate that low, medium and high N rates produced an average IWG biomass of 7.8, 9.7 and 10.5 t ha-1 , in addition to observed grain yield of 0.36, 0.49 and 0.45 t ha-1, respectively. The corresponding N rates produced 5.9, 7.9 and 8.7 t ha-1 maize yield. Soil profile moisture under IWG and maize averaged 0.25 and 0.29 m3m-3, respectively. Averaged over N rates and locations, IWG and maize had values for crop evapotranspiration (ETc) of 592 vs 517 mm; deep percolation of 100.8 vs 154.5 mm; and nitrate-N leaching losses of 2.6 vs 17.9 kg ha-1, respectively. Results indicate that perennial IWG not only produced high biomass under rainfed conditions, but also reduced deep percolation by efficiently using soil profile moisture, leading to nitrate-N leaching losses six to seven times lower than for maize.